Evaluation of Wireless Solar Power Transfer System Performance in Partial Shadowing Situation - Gultom, Togar Timoteus; Irwanto, Muhammad (Faculty of Engineering, Universitas Tanjungpura, 2025)
The wireless solar power transfer (WSPT) system is impacted by solar radiation that arrives on the surface of the solar module. The objective of the research is to evaluate the performance of the WSPT system under a shadowing situation. The method of this research is that the solar module and WSPT are modeled and simulated using MATLAB SIMULINK. Three solar modules with different degrees of solar irradiation are subjected to it. The research results indicate that to meet the system frequency of 50 Hz and match the frequency of both coils, the inductance of the transmitter and receiver coils, which is 0.1689 H, should be connected in parallel to a capacitor of 60 µF. It shows that the three solar modules connected in series have an output voltage of 177 V. It shows that the WSPT system and solar modules' performance are impacted by the shadowing situation. Higher shadowing levels will lessen the amount of sunlight that reaches the solar modules' surface. It implies that both the WSPT system's performance and that of the solar modules will decline concurrently.